The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3389/fmicb.2016.00693
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Mycoplasma pneumoniae Infections in Japan and Therapeutic Strategies for Macrolide-Resistant M. pneumoniae

Abstract: Pneumonia caused by Mycoplasma pneumoniae (M. pneumoniae pneumonia) is a major cause of community-acquired pneumonia worldwide. The surveillance of M. pneumoniae pneumonia is important for etiological and epidemiological studies of acute respiratory infections. In Japan, nation-wide surveillance of M. pneumoniae pneumonia has been conducted as a part of the National Epidemiological Surveillance of Infectious Diseases (NESID) program. This surveillance started in 1981, and significant increases in the numbers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
121
3
7

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(137 citation statements)
references
References 104 publications
6
121
3
7
Order By: Relevance
“…This and several previous studies demonstrated that most strains of MLVA type 3-5-6-2 were P1 type 2 or its variant, whereas MLVA type 4-5-7-2 was P1 type 1 (9,(11)(12)(13)21,30). Therefore, the increase in MLVA type 3-5-6-2 after 2011 may be a type-shift phenomenon of M. pneumoniae P1 types (7).…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…This and several previous studies demonstrated that most strains of MLVA type 3-5-6-2 were P1 type 2 or its variant, whereas MLVA type 4-5-7-2 was P1 type 1 (9,(11)(12)(13)21,30). Therefore, the increase in MLVA type 3-5-6-2 after 2011 may be a type-shift phenomenon of M. pneumoniae P1 types (7).…”
Section: Discussionsupporting
confidence: 68%
“…Epidemics of M. pneumoniae infections have been observed in 3-to 7-year intervals in many areas worldwide (7). In Japan, a large epidemic of M. pneumoniae infections was observed between 2011 and 2013 (29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Excessive use of macrolides and quinolones for respiratory infections has been a major concern in Japan,28 because of their possible association to high macrolide resistance rates among Streptococcus pneumoniae 29 and M. pneumoniae ,7 and increased quinolone resistance among Enterobacteriaceae 30. Besides the reduction in antibiotic use, we consider that rapid diagnoses and early initiation of effective treatment may prevent the transmission of M. pneumoniae and consequently reduce the spread of macrolide‐resistant M. pneumoniae .…”
Section: Discussionmentioning
confidence: 99%